12. CHARACTERISTICS CLINICAL OF DYSMENORRHEA AND THE NEED FOR TREATMENT WITH TRADITIONAL MEDICINE OF FEMALE STUDENTS OF CAN THO UNIVERSITY OF MEDICINE AND PHARMACY IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: Survey on the rate of dysmenorrhea and clinical characteristics of dysmenorrhea according to traditional medicine and modern medicine among female students at Can Tho University of Medicine and Pharmacy in 2023. Survey on used measures and desired treatment Menstrual dysmenorrhea with traditional medicine for female students at Can Tho University of Medicine and Pharmacy in 2023.Materials and methods: Cross-sectional descriptive study on 211 full-time female students in 9 majors of Can Tho University of Medicine and Pharmacy in 2023. Students were guided and filled out a set of prepared questions, using 17 signs based on RSS - Cox scale to evaluate the rate of symptoms and using the VAS pain scale to evaluate the level of pain.Results: Through the above survey, the rate of dysmenorrhea among female students at Can Tho University of Medicine and Pharmacy in 2023 is 88.2%. Moderate pain level (according to VAS) accounts for 49.2%, mild pain 30.5% and severe pain 20.3%. According to traditional medicine, positive symptoms account for 22.9%, false symptoms 71.1%, heat symptoms 0.5% and cold symptoms 13.9%. Regarding the clinical form, the qi and blood deficiency type accounts for the highest rate of 51.9%. The percentage of students using pain relief methods is 55.7%, of which 63/107 students use medication and 44/107 students use non-medication methods. The percentage of students needing treatment with traditional medicine is 48.7%.Conclusions: Dysmenorrhea is a common condition among female students at Can Tho University of Medicine and Pharmacy. Pain level according to VAS is mainly moderate pain. According to Traditional Medicine, most dysmenorrhea is a symptom of dysmenorrhea with the main clinical form being weak qi and blood and many students want to learn and treat dysmenorrhea using Traditional Medicine.
Keywords: Dysmenorrhea, the need for treatment, female students, non-medication methods, treatment with traditional medicine, Can Tho University of Medicine and Pharmacy.